Understanding their Voices from Within: Difficulties and Code Comprehension of Life-Long Novice Programmers - Javier, Billy (International Journal of Arts, Sciences and Education, 2021)
Programming is considered one of the grand challenges in computing education and attracts much attention in computing education research. Most areas of concerns were in to teaching methods, educational technologies, and student performance. This study uncovers the difficulties and code comprehension of novice programmers with the hope of providing efforts to computing institutions in improving programming competencies of novice programmers. Qualitative interview, observation, and document reviews were the methods in data collection towards understanding the voices within the thirteen (13) junior Information Technology life-long learners consented to participate in this mixed-method study. The participants were subjected to a hands-on experience, program tracing or debugging, and interviews along the process. Results showed the novice programmers’ difficulties in program structures, code comprehension, program tracing or debugging, as well as code navigation. The results imply a growing concern for course designers in restructuring course methodologies providing real-world problem-solving cases and understanding the student’s dilemma in writing, designing, code comprehension and tracing, as well as navigating the code. The current study was limited to understanding the difficulties and code comprehension among novice programmers, thus a future work to consider the teachers’ difficulties and issues associated to novice programmers may be necessary.